Green Financial or Greenwashing? Bank Mandiri’s Innovation in Support of Net Zero Emission 2060 - Wibowo, Bromo Yudo; Al-Fadhat, Faris (Jurnal Hubungan Internasional, 2026)
This study analyzed Bank Mandiri’s position in the political economy of Indonesian banking, emphasizing the possibility of greenwashing in the offering of green loans and sustainability-linked loans. As of June 2024, Bank Mandiri possessed a sustainable portfolio worth IDR 278 trillion. The bank’s green portfolio grew by 20.4% annually to IDR 139 trillion. This study adopted a qualitative method by analyzing Bank Mandiri’s annual financial reports from 2020 to 2024, public policies, and online news media coverage to evaluate its alignment with the net-zero emission (NZE) 2060 commitment. The findings unveiled that although funds have been allocated to renewable energy projects such as hydro and geothermal, most funds remained flowing into sectors with high environmental risks, such as the development of smelters that rely on fossil fuels, contradicting the NZE goals. Bank Mandiri’s ESG program has not yet met all crucial sustainability standards, indicating the presence of greenwashing practices. Indonesia does not possess mandatory sustainability reporting standards, but it has encouraged reporting based on global standards, such as GRI and the newly adopted IFRS standards. This study emphasizes the significance of greater transparency and government oversight to ensure that green financing truly benefits the environment and is not merely a marketing strategy. The novelty of this research lies in the lack of studies conducted on the financing policies provided by Mandiri Bank. This study analyzed Bank Mandiri’s position in the political economy of Indonesian banking, emphasizing the possibility of greenwashing in the offering of green loans and sustainability-linked loans. As of June 2024, Bank Mandiri possessed a sustainable portfolio worth IDR 278 trillion. The bank’s green portfolio grew by 20.4% annually to IDR 139 trillion. This study adopted a qualitative method by analyzing Bank Mandiri’s annual financial reports from 2020 to 2024, public policies, and online news media coverage to evaluate its alignment with the net-zero emission (NZE) 2060 commitment. The findings unveiled that although funds have been allocated to renewable energy projects such as hydro and geothermal, most funds remained flowing into sectors with high environmental risks, such as the development of smelters that rely on fossil fuels, contradicting the NZE goals. Bank Mandiri’s ESG program has not yet met all crucial sustainability standards, indicating the presence of greenwashing practices. Indonesia does not possess mandatory sustainability reporting standards, but it has encouraged reporting based on global standards, such as GRI and the newly adopted IFRS standards. This study emphasizes the significance of greater transparency and government oversight to ensure that green financing truly benefits the environment and is not merely a marketing strategy. The novelty of this research lies in the lack of studies conducted on the financing policies provided by Mandiri Bank.